KEMITRAAN PT PASANGKAYU DALAM PROGRAM PENYEDIAAN AIR BERSIH DI KELURAHAN MARTAJAYA: Indonesia - Akram Gafar Daud; Alysa Putri; Ibrahim; Dita Ananta; Tri Fania; Riana; Grasela Peluru; Nawawi Natsir; Fiki Ferianto; Nuraisyah (CV. KAMPUSA AKADEMIK PUBLISING, 2026)
The primary objective of this research is to evaluate the collaborative efforts and partnership among PT Pasangkayu, the Martajaya Village Government, and the local residents regarding the execution of a clean water provision initiative. A qualitative descriptive approach was utilized to thoroughly examine the cooperation patterns, gathering data via direct observations, interviews, and documentation. Findings reveal a successful and effective synergy where PT Pasangkayu supplied the necessary water infrastructure sourced from mountain springs, the village administration served as the coordinating facilitator, and the locals actively engaged in utilizing and preserving the provided facilities. Roughly 45 families have reaped the benefits of this project, which has fundamentally enhanced water accessibility and addressed water shortages, notably during drought periods. Additionally, this ongoing teamwork has forged stronger bonds and cooperation between the corporation, the government, and the citizens. To ensure the long-term viability of these benefits, a unified commitment and active participation from all involved parties is essential for the continuous maintenance of the infrastructure.